2023
DOI: 10.1017/s0022149x23000123
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of helminth parasites

Abstract: Next generation sequencing technologies have facilitated a shift from a few targeted loci in population genetic studies to whole genome approaches. Here, we review the types of questions and inferences regarding the population biology and evolution of parasitic helminths being addressed within the field of population genomics. Topics include parabiome, hybridization, population structure, loci under selection and linkage mapping. We highlight various advances, and note the current trends in the field, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 180 publications
1
1
0
Order By: Relevance
“…In contrast, Wadhwa et al [57], Velusamy et al [58], and Das et al [43] observed a lower, i.e., 10-55%, prevalence of gastrointestinal nematode parasites and gastrointestinal protozoan parasites in ruminants. Similar reports on parasite prevalence rates are also available in the literature from different geographical regions of the world [36,37,59,60]. It was also observed that the female animals had a slightly higher infestation with gastrointestinal parasites as compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, Wadhwa et al [57], Velusamy et al [58], and Das et al [43] observed a lower, i.e., 10-55%, prevalence of gastrointestinal nematode parasites and gastrointestinal protozoan parasites in ruminants. Similar reports on parasite prevalence rates are also available in the literature from different geographical regions of the world [36,37,59,60]. It was also observed that the female animals had a slightly higher infestation with gastrointestinal parasites as compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 81%
“…Livestock farming is indispensable for the sustainability of the rural economy in India, including the northern state of Himachal Pradesh. However, gastrointestinal nematodes and gastrointestinal protozoa in domesticated ruminants are known to exert tremendous economic losses by adversely impacting animal health, productivity, yields, and reproduction [20,25,[35][36][37]. Moreover, these infections are often neglected by livestock owners and result in significant economic losses in the long term [20].…”
Section: Discussionmentioning
confidence: 99%